Tax Violation in Panama Papers - Miranti Verdiana; Ryamirzad Ryamirzad; Ita Fattumah; Ragil Kusnaning Rini; Devi Sukma Ayuningtyas (Journal La Bisecoman, 2020)
The aim of this research is to find out the relationship between the Panama Papers and the existence of criminal actions in Taxation. The Panama Papers is the name for a document that was created by a company from Panama called Mossack Fonseca, which contains detailed information on more than 214,000 overseas companies, including the identities of their shareholders and directors. This case is an international scale leak of financial documents that reveals how 12 heads of state have a company in an undisclosed tax free jurisdiction (offshore). This leaked document was then distributed to and analyzed by approximately 400 journalists in 107 media organizations in more than 80 states. The research conclusions show that the disclosure of the Panama Papers scandal proves clearly that tax which is mandatory and binding is considered a serious burden for the upper class that is involved in this case. Millions of secret financial documents were leaked and revealed how the corruption and tax crime network of heads of state, secret agents, celebrities to fugitives are hidden in tax haven. The scandal that was revealed would have caused the State to lose or reduce the state's wealth (asset forfeiture) which was quite significant. And the relationship between the case and the violation of tax law is that the mistake is deliberate or the mistake is fraudulent.